How Green Investment Affects Stock Returns: Exploring the Role of Financial Performance - Putrika, Uun; Ardianto (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Green investment is increasingly recognized as a key driver of financial and environmental sustainability. Specific Background: While prior research has examined its impact on stock returns, limited studies focus on emerging markets and the moderating role of financial performance. Knowledge Gap: The relationship between green investment and stock returns remains unclear, particularly regarding the influence of Return on Assets (ROA). Aims: This study investigates the effect of green investment on stock returns and examines whether ROA moderates this relationship. Methods: A quantitative approach was applied to panel data from 10 SRI KEHATI-listed companies (2019–2023). Green investment was measured using the PROPER rating system, and panel regression analysis was conducted. Results: Findings indicate that green investment positively influences stock returns, with ROA strengthening this effect. Novelty: This study extends the literature by focusing on an emerging market and integrating ROA as a moderating factor. The use of PROPER ratings adds a novel environmental performance metric. Implications: The results highlight the need for firms to align green investment strategies with financial efficiency, offering insights for investors and policymakers to promote sustainability-driven financial growth